Kemarau di lembah - Kassim Ahmad, 1933- (Kuala Lumpur : Teks Publishing, 1985)
Short stories and poems in Malay; some poems with parallel translation in English.
mayeng
1
4
Koleksi sumbangan Prof. Dr. Ding Choo Ming
Keywords: Malay fiction